Functional Potential of Katoikonyms (Exemplified by 20th – 21st Century Volgograd Regional Newspapers) - Kirillova, Svetlana (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2022)
Katoikonyms, which nominate residents, and their functioning in the language of Volgograd (Stalingrad) region media are in the focus of research. The facts revealed in the texts of local newspapers of different periods (1941–1945, 1985–1991 and 2010–2021) contributed to the characteristics of the units under study. The main and additional functions of the names of residents were revealed. The main functions, the implementation of which is not conditioned by context, include nominative, associated with the naming of a significant for a native speaker object of reality, and compressive, connected with the transmission of information about a locality in a compressed form. Contextually stipulated additional functions include address, which reflects the replacement of a toponym with a derivative katoikonym; text-forming, which enables the transmission of knowledge about the content of material before acquaintance with it, memorial-local, which causes associations about cultural and historical heritage, as well as differentiating, which helps to distinguish people by the territory of dwelling, identifying that emphasizes a person's belonging to the area of residence, stylistic (play on words with a katoikonym), and temporal (localization of the subjects of the narrative in a specific time period) functions. The paper describes the conditions for the implementation of the additional functions. The use of derivatives that demonstrate relatively stable tendencies to perform certain functions in local media within different time periods has been characterized.